Rate of RhD-alloimmunization after the transfusion of RhD-positive red blood cell containing products among injured patients of childbearing age: single center experience and narrative literature review. Issue 1 (1st January 2021) - Yazer, Mark; Triulzi, Darrell; Sperry, Jason; Corcos, Alain; Seheult, Jansen
ABSTRACT: Objectives: To determine the rate of RhD-alloimmunization in injured RhD-negative patients in the age range of childbearing potential who were transfused with at least one unit of RhD-positive red blood cells (RBC) or low titer group O whole blood (LTOWB). Methods: Injured RhD-negative patients between the ages of 13–50 at an American Level 1 trauma center who were transfused with at least one unit of RBCs or LTOWB during their resuscitation and who had an antibody detection test performed at least 14 days afterwards were included. Results: Over a 20-year period, 96 study-eligible patients were identified, of which 90/96 (93.8%) were male. The median age of these 96 patients was 33 (5th–95th percentiles: 19–49) years. The majority of these patients (71/96, 74.0%) had an injury severity score (ISS) greater than 15. Overall, 41/96 (42.7%; 95% CI: 32.7%–53.2%) of these patients became alloimmunized after receipt of a median of 3 (5th–95th percentiles: 1–35) units of RhD-positive RBCs and/or LTOWB. There was no association between receipt of leukoreduced RBCs or receipt of LTOWB and the RhD-alloimmunization rate. Discussion: The rate of RhD-alloimmunization in this study was at the higher end of rates that have been reported. None of the previous studies focused exclusively on trauma patients in the childbearing age range. Conclusion: The 42.7% rate of RhD-alloimmunization in a predominantly male trauma population could probably be extrapolated to women in the same age range when estimating their risk of RhD-alloimmunization following RhD-positive transfusion.